The beaten paths effect on patient inter‐regional mobility: An application to the Italian NHS. Issue 4 (3rd May 2022) - Berta, Paolo; Martini, Gianmaria; Spinelli, Daniele; Vittadini, Giorgio
Abstract: We study inter‐regional migration flows due to hospital admissions and focus on the impact of migration beaten paths. We estimate a gravity model applied to Italian data for the period 2010–2016. We find that beaten paths have a positive effect on inter‐regional patient flows, with estimated elasticity equal to +0.32%. Therefore, family and social ties among people living in the region of origin and destination for hospital admissions may explain the concentration of health migration (HM) in some regions. Moreover, the beaten path effect is stronger for private hospitals. We also find that HM patients are more sensible to hospital quality than those admitted in local hospitals. Resumen: Se estudiaron los flujos migratorios interregionales debidos a los ingresos hospitalarios y el estudió se centró en el impacto de las trayectorias migratorias habituales. Se estimó un modelo de gravedad aplicado a datos italianos para el periodo 2010–2016. Se encontró que las rutas habituales tienen un efecto positivo en los flujos interregionales de pacientes, con una elasticidad estimada de +0, 32%. Por lo tanto, los lazos familiares y sociales entre las personas que viven en la región de origen y destino de los ingresos hospitalarios pueden explicar la concentración de la migración sanitaria (MS) en algunas regiones. Además, el efecto de las trayectorias habituales es más fuerte para los hospitales privados. También se encontró que los pacientes involucrados en MS están más influidos por la calidad del hospital que los ingresados en hospitales locales. 抄録: 本稿では、医療機関への入院による地域間の移住の流れを検討し、移住の通常の経路(migration beaten path)の影響に焦点を当てる。2010~2016年のイタリアのデータに適用した重力モデルを用いて推計する。この通常の経路が地域間の患者の流れに対してプラスの影響を及ぼしており、推定弾力性が+0.32%に等しいことが分かった。すなわち、家族及び入院の際の出発地と目的地の地域に住む人々との社会的なつながりが、一部の地域における健康移住(health migreation)の集中の原因を明らかにする可能性がある。さらに、beaten path効果は民間病院の方が強い。また、健康移住をする患者は、地域の病院に入院した患者よりも病院の質に敏感であると考えられる。